The Evaluation of Bedadung Watershed Continuance in Jember Region - Kusuma, Desy Lainufarsari (Kern : Jurnal Ilmiah Teknik Sipil, 2011)
The change of land around Bedadung watershed is influenced by the rate of population growth. The higher rate ofpopulation growth is in line with the required land necessity. In this case, the performance of watershed management isneeded to improve the function of both land and water area. This research aims to know the result of the examinedparameters classification including the parameters of water system, land use, social aspects, economic, and watershedinstitutions. This study used the calculation method in accordance with the Regulation of Director General of LandRehabilitation and Social Forestry on Guidelines for Monitoring and Evaluation of Watersheds (SK Dirjen RLPS2009). The research that was conducted in Bedadung watershed of Jember Regency which has 138319,6 hectares ofland area resulted that watershed performance with the parameter of water system is 1,475 in 2001 and 1,53 in 2017.Therefore, both of them are included into a good category with the value <1,7. Meanwhile, the watershed performancewith water catchment parameters in 2001 is 1,95 and 2,15 in 2017. Thus, both are included into passable category witha value of 1,7 - 2,5. The results of Bedadung watershed performance in 2001 is 1,6915 and it is considered as anexcellent condition with the value < 1,7. The results of Bedadung watershed performance in 2017 is 1,8143 andincluded into decent category with the value 1,7 â 2,5. Therefore, it can be concluded that the performance of Bedadungwatershed in 2017 is decreasing if it is compared to the performance of Bedadung watershed in 2001.Keywords: Bedadung Watershed, Evaluation, Performance